2022
DOI: 10.3390/ijms232113484
|View full text |Cite
|
Sign up to set email alerts
|

Radical Production with Pulsed Beams: Understanding the Transition to FLASH

Abstract: Ultra-high dose rate (UHDR) irradiation regimes have the potential to spare normal tissue while keeping equivalent tumoricidal capacity than conventional dose rate radiotherapy (CONV-RT). This has been called the FLASH effect. In this work, we present a new simulation framework aiming to study the production of radical species in water and biological media under different irradiation patterns. The chemical stage (heterogeneous phase) is based on a nonlinear reaction-diffusion model, implemented in GPU. After t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…However, increasing the duration of the pulse relative to the pulse repetition period increases the fraction of the total treatment time where the system stays at saturation. This feature of the model gives rise to different predictions from those of other modeling efforts which do not incorporate saturation, such as [17]. This is an important prediction which could eventually be validated or refuted based on future experimental work.…”
Section: Study Of the Model: Parameters And Comparison To Literature ...mentioning
confidence: 95%
See 2 more Smart Citations
“…However, increasing the duration of the pulse relative to the pulse repetition period increases the fraction of the total treatment time where the system stays at saturation. This feature of the model gives rise to different predictions from those of other modeling efforts which do not incorporate saturation, such as [17]. This is an important prediction which could eventually be validated or refuted based on future experimental work.…”
Section: Study Of the Model: Parameters And Comparison To Literature ...mentioning
confidence: 95%
“…Since a value of 40 Gy/s is often given as a threshold for FLASH effect reproduced in in vivo experiments, we have chosen this same value for our parameter D 0 /τ . To select individual values for D 0 and τ, we consider the characteristic time τ 1 μs, similar to the kinetic constant of many relevant reactions and often used as a threshold for the homogeneous phase of the reaction process [17,7]. Therefore, to maintain a dose rate threshold D 0 /τ 40 Gy/s, we select a value of D 0 4 10 -5 Gy.…”
Section: Study Of the Model: Parameters And Comparison To Literature ...mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Furthermore, it has been shown that the onset of the FLASH effect is deeply influenced by the beam pulse structure (instantaneous dose-rate, dose-per-pulse or the number of pulses) as it modifies the cell's exposure to free radicals. [2][3][4][5] Therefore, fast and accurate monitoring of the time structure of the beam is vital for FLASH treatments, which challenges existing solutions. Bunch monitors are also crucial for some range verification techniques in particle therapy that rely on the prompt-gamma ray production within the patient.…”
Section: Introductionmentioning
confidence: 99%
“…It is often assumed that the time scale related to the FLASH effect is larger than the duration of a pulse so that the dose rate may be considered constant during the delivery of a spot [15][16][17] (∼1-10 ms) hence unchanged between pulsed or continuous delivery, 18 although this remains to be further demonstrated. 9 Nevertheless, in PBS, the total dose received by a voxel is generally the sum of the contributions of several spots.…”
Section: Introductionmentioning
confidence: 99%